Chubutolithes gaimanensis and other wasp ichnofossils: breaking through the taphonomic barrier - Genise, Jorge Fernando (2004)
Wasp ichnofossils are scarce in the record because of their low preservational potential. Evidence comprises perforations in bee cells, cocoons, and paper and mud nests, whose preservation may involve the most unusual taphonomic processes. The record includes trace fossils preserved in other trace fossils; paper nests preserved in amber, ironstones and caves; and fragile trace fossils preserved in conglomerates. Evidence for wasps is weak  in some cases and more reliable in others. Perforations in bee cells can be attributed to other insects;  likewise cocoons can be attributed to other insects and other organic and inorganic processes. Some fossil paper and mud nests are the most reliable wasp ichnofossils. Brownichnus favosites preserved in ironstone and in Dominican amber, provide the oldest records of polistines known. One of the best-known examples of wasp ichnofossils is Chubutolithes gaimanensis, preserved in intraclast conglomerates. New ichnological and sedimentological evidence suggests that cells were constructed around plant stems from which they could have dropped to the soil, been covered with sediments, impregnated with carbonate, and then reworked by fluvial action along with other carbonate nodules.